Satellite Earth observation data to identify anthropogenic pressures in selected protected areas - Nagendra, Harini; Mairota, Paola; Marangi, Carmela; Lucas, Richard; Dimopoulos, Panayotis; Honrado, João Pradinho; Niphadkar, Madhura; Mücher, Caspar A.; Tomaselli, Valeria; Panitsa, Maria; Tarantino, Cristina; Manakos, Ioannis; et al. (ITC journal, 2015)
•Parks experience stress from human pressures, which require mapping and monitoring.•Earth observation (EO) data can monitor changes in state resulting from pressure over time.•Impact on landscapes, habitats and species communities can be related to pressure.•EO data useful for monitoring pressure and changes in state are listed for parks in six countries.•The approach is illustrated in two contexts in Italy and The Netherlands. Protected areas are experiencing increased levels of human pressure. To enable appropriate conservation action, it is critical to map and monitor changes in the type and extent of land cover/use and habitat classes, which can be related to human pressures over time. Satellite Earth observation (EO) data and techniques offer the opportunity to detect such changes. Yet association with field information and expert interpretation by ecologists is required to interpret, qualify and link these changes to human pressure. There is thus an urgent need to harmonize the technical background of experts in the field of EO data analysis with the terminology of ecologists, protected area management authorities and policy makers in order to provide meaningful, context-specific value-added EO products. This paper builds on the DPSIR framework, providing a terminology to relate the concepts of state, pressures, and drivers with the application of EO analysis. The type of pressure can be inferred through the detection of changes in state (i.e. changes in land cover and/or habitat type and/or condition). Four broad categories of changes in state are identified, i.e. land cover/habitat conversion, land cover/habitat modification, habitat fragmentation and changes in landscape connectivity, and changes in plant community structure. These categories of change in state can be mapped through EO analyses, with the goal of using expert judgement to relate changes in state to causal direct anthropogenic pressures. Drawing on expert knowledge, a set of protected areas located in diverse socio-ecological contexts and subject to a variety of pressures are analysed to (a) link the four categories of changes in state of land cover/habitats to the drivers (anthropogenic pressure), as relevant to specific target land cover and habitat classes; (b) identify (for pressure mapping) the most appropriate spatial and temporal EO data sources as well as interpretations from ecologists and field data useful in connection with EO data analysis. We provide detailed examples for two protected areas, demonstrating the use of EO data for detection of land cover/habitat change, coupled with expert interpretation to relate such change to specific anthropogenic pressures. We conclude with a discussion of the limitations and feasibility of using EO data and techniques to identify anthropogenic pressures, suggesting additional research efforts required in this direction.